Acute Pancreatitis Review - Huang, Yuting; Badurdeen, Dilhana S. (Turkish Journal of Gastroenterology, 2023)
Acute pancreatitis, a prevalent illness with devastating consequences, poses a grave threat to those affected. There has been a steady increase in the occurrence of acute pancreatitis at about 3% per year from 1961 to 2016. There are 3 main guidelines on acute pancreatitis, including the American College of Gastroenterology, the International Association of Pancreatology/American Pancreatic Association guideline in 2013, and the American Gastroenterological Association guideline in 2018. However, several milestone studies have been published since then. We hereby reviewed the current acute pancreatitis guidelines with an update on clinical practicechanging literature. The aggressive or moderate fluid resuscitation in acute pancreatitis (WATERFALL) trial recommended fluid resuscitation with lactated Ringer’s solution at a moderate aggressive rate. All guidelines did not recommend prophylactic antibiotics use. Early enteral feeding reduces morbidity. A clear liquid diet is no longer recommended. Nutrition with nasogastric or nasojejunal feeding does not have a difference. The upcoming high vs. low-energy administration in the early phase of acute pancreatitis (GOULASH) trial will provide more information on the impact of calorie intake. Pain management should be individualized based on the degree of pain and severity of pancreatitis. In patients with moderate to severe and severe acute pancreatitis, a step-down approach with epidural analgesia can be considered for moderate to severe pain. The management of acute pancreatitis has evolved. New research on the impact of electrolytes, pharmacologic agents, the role of anticoagulants, and nutrition support will provide scientific and clinical evidence to improve patient care and decrease morbidity and mortality. Cite this article as: Huang Y, Badurdeen DS. Acute pancreatitis review. Turk J Gastroenterol. 2023;34(8):795-801.